The effects of hive materials on phytochemical and biological properties of honeybee propolis. Issue 10 (5th October 2022) - Kegode, Timothy M.; Lattorff, H. Michael G.
Abstract: Background: Propolis has been of interest due to its indisputably rich chemical composition. It has gained attention in recent years because of its potential biological properties, such as antibacterial, cariostatic, antioxidant, and hepatoprotective. Therefore, there has been an increased demand for ways to benefit from these potential impacts by enriching the nutritional value, quality, and functionality of food products. Propolis antioxidants, antibacterial, and antifungal properties make it useful in food technology. Our present study was conducted to investigate the effects of beehive material on the phytochemical and bio‐functional properties of propolis. In this study, propolis was obtained from three different hive types: concrete, mud, and wood. The phytochemical content and bioactivities of the samples were analysed. Total phenolic content (TPC), total terpenoid content (TTC), total flavonoid content (TFC), total alkaloid content (TAC), 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) antioxidant capacity, and antibacterial activity were determined. Results: The highest phytochemical composition was determined in concrete beehives, followed by mud hives and wood hives in this study. Likewise, for bioactivities, concrete hives demonstrated a high level of both antioxidant activity and antibacterial activity for both Gram‐positive and Gram‐negative bacteria. Conclusion: This suggests that the hive material shows a noticeable effect on propolis biochemical properties, apart from being influenced by climate and vegetation.